2014
DOI: 10.1167/iovs.13-13625
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mutations Causing Inherited Retinal Degenerations in the Israeli and Palestinian Populations Using Homozygosity Mapping

Abstract: Homozygosity mapping is a powerful tool to identify genetic defects underlying heterogeneous AR disorders, such as RP and LCA, in consanguineous and nonconsanguineous patients. The identification of significant and large homozygous regions, which do not include any known retinal disease genes, may be a useful tool to identify novel disease-causing genes, using next generation sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 65 publications
3
33
1
Order By: Relevance
“…Another study closely followed and reported 11 distinct RDH12 mutations in homozygosity or compound heterozygosity in 8/44 patients with LCA who were affected with the congenital severe yet progressive rod-cone dystrophy form of the disease [16]. To date, over 60 different RDH12 mutations have been reported predominantly in LCA patients [1517, 21, 2327] but also in early-onset retinal dystrophy [8, 15, 20, 21, 24, 25], in families with arRP [26, 27], and in a family with autosomal dominant RP [19]. These findings above have shown that mutations in the human RDH12 gene are responsible for severe forms of blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Another study closely followed and reported 11 distinct RDH12 mutations in homozygosity or compound heterozygosity in 8/44 patients with LCA who were affected with the congenital severe yet progressive rod-cone dystrophy form of the disease [16]. To date, over 60 different RDH12 mutations have been reported predominantly in LCA patients [1517, 21, 2327] but also in early-onset retinal dystrophy [8, 15, 20, 21, 24, 25], in families with arRP [26, 27], and in a family with autosomal dominant RP [19]. These findings above have shown that mutations in the human RDH12 gene are responsible for severe forms of blindness.…”
Section: Discussionmentioning
confidence: 99%
“…7 From 2000 to the present day, approximately half of the published studies diagnose patients with TULP1 mutations as having LCA or EORD. [8][9][10][11][12][13][62][63][64] The remainder categorize the disease as arRP, but note childhoodonset vision loss and night blindness. 14,62,[65][66][67][68] Regardless of clinical diagnosis, early-onset night blindness, visual acuity loss and nystagmus are common findings.…”
Section: Discussionmentioning
confidence: 99%
“…A recentlyreported mutation (D94Y) is the only missense mutation located outside of the tubby domain. 64 How does the current study add to the understanding of the phenotype of patients with TULP1 mutations? Serial kinetic field data, over 5 to 10 years in some of the patients, indicate five different genotypes, three parameters were measured at the fovea: ONL and COS thicknesses, and visual sensitivity (dark-adapted, 650 nm).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygosity mapping was performed using whole genome single-nucleotide polymorphism microarrays (Affymetrix 6.0) as reported previously 23. WES analyses were performed on DNA samples of 64 individuals at Otogenetics (Norcross, Georgia, USA) using different approaches and were grouped accordingly: group 1 (G1)—43 samples using Agilent V4 and Illumina HiSeq 2000 with a 30× coverage (hg19), G2—10 samples using Numblegen V2 and PE100 Illumina HiSeq 2000 with a 30× coverage (hg19), G3—4 samples using Agilent Human exome V5 and PE100 HiSeq 2000/2500 with a 50× coverage (hg19), G4—4 samples using Agilent Human exome V5 and PE100 HiSeq 2000/2500 with a 50× coverage (hg38) and G5—3 samples using Agilent Human exome V5 and PE100 HiSeq 2000/2500 with a 100× coverage (hg19).…”
Section: Methodsmentioning
confidence: 99%